Longitudinal Changes of Circulating miRNAs During Bisphosphonate and Teriparatide Treatment in an Animal Model of Postmenopausal Osteoporosis. (10th March 2021) - Weigl, Moritz; Kocijan, Roland; Ferguson, James; Leinfellner, Gabriele; Heimel, Patrick; Feichtinger, Xaver; Pietschmann, Peter; Grillari, Johannes; Zwerina, Jochen; Redl, Heinz; Hackl, Matthias
ABSTRACT: MicroRNAs regulate bone homeostasis, and circulating microRNAs have been proposed as novel bone biomarkers. The effect of anti‐osteoporotic treatment on circulating microRNAs has not been described in detail. Therefore, we performed a comprehensive analysis of microRNA serum levels in ovariectomized (OVX) and sham‐operated (SHAM) rats over 12 weeks of antiresorptive or osteoanabolic treatment. Forty‐two Sprague Dawley rats underwent SHAM surgery ( n = 10) or ovariectomy ( n = 32). After 8 weeks, OVX rats were randomized to antiresorptive treatment with zoledronate ( n = 11), osteoanabolic treatment with teriparatide ( n = 11), or vehicle treatment ( n = 10). Serum samples were collected at weeks 8, 12, 16, and 20 after surgery. A total of 91 microRNAs were analyzed by RT‐qPCR in serum samples collected at week 20. Based on the results, 29 microRNAs were selected for longitudinal analysis at all four study time points. Changes in bone mineral density and microstructure were followed up by in vivo micro‐CT and ex vivo nano‐CT. Ovariectomy resulted in the loss of trabecular bone, which was reversed by osteoanabolic and antiresorptive treatment. Differential expression analysis identified 11 circulating miRNAs that were significantly regulated after treatment. For example, miR‐107 and miR‐31‐5p increased in vehicle‐treated OVX animals, whereas they decreased during teriparatide treatment. Additional miRNAs were identified that showed significant correlations to bone microstructure or bone miRNA expression, including miR‐203a‐3p, which exhibited a significant negative correlation to vertebral and tibial trabecular bone volume fraction (%). Longitudinal analysis confirmed eight microRNAs with significant changes in serum over time that were prevented by teriparatide and zoledronate treatment (miR‐34a‐5p, miR‐31‐5p, miR‐30d‐3p, miR‐378a‐5p) or teriparatide treatment only (miR‐375‐3p, miR‐183‐5p, miR‐203a‐3p, miR‐203b‐3p). Gene target network analysis identified WNT and Notch signaling as the main signaling pathways controlled by these miRNAs. Thus, ovariectomy results in time‐dependent deregulation of circulating miRNAs compared with SHAM animals. Anti‐osteoporotic treatments can rescue this effect, showing that bone‐related miRNAs might act as novel biomarkers for treatment monitoring. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).